Empowering Primary School Students Through Problem-Based Learning: A Path to Literacy and Numeracy Mastery - Siregar, Rosliana; Siagian, Muhammad Daut; Syahlan, Syahlan (Mosharafa: Jurnal Pendidikan Matematika, 2024)
Abstrak Keterampilan literasi dan numerasi sangat penting untuk mencapai potensi penuh dalam menjalani kehidupan yang bermakna dan produktif. Penelitian ini bertujuan mengkaji efektivitas Problem-Based Learning (PBL) dalam meningkatkan literasi dan numerasi siswa sekolah dasar di Kota Medan. Menggunakan desain quasi-eksperimen, sampel terdiri dari 37 siswa kelompok eksperimen (PBL) dan 35 siswa kelompok kontrol (konvensional). Data dikumpulkan melalui tes prior knowledge (PK), literasi, dan numerasi, dianalisis dengan ANOVA dua jalur. Hasil menunjukkan bahwa kelompok eksperimen mengalami peningkatan signifikan, dengan N-Gain literasi (0.449) dan numerasi (0.439) lebih tinggi dibanding kelompok kontrol (0.268 dan 0.236). Selain itu, PK berpengaruh signifikan terhadap numerasi, tetapi tidak terhadap literasi. Penelitian ini merekomendasikan integrasi PBL dalam kurikulum untuk meningkatkan keterampilan siswa serta penelitian lanjutan terkait motivasi dan konteks sosial-budaya. PBL terbukti sebagai pendekatan inovatif yang relevan bagi peningkatan kualitas pendidikan di Indonesia. Abstract Literacy and numeracy skills are essential for individuals to reach their full potential, lead meaningful and productive lives, and participate fully in society. This study aims to examine the effectiveness of Problem-Based Learning (PBL) in enhancing the literacy and numeracy skills of primary school students in Medan, Indonesia. Employing a quasi-experimental design, the study involved 37 students in the experimental group (PBL) and 35 students in the control group (conventional learning). Data were collected through prior knowledge (PK) tests, as well as literacy and numeracy assessments, and analyzed using two-way ANOVA. The results revealed that the experimental group showed significantly greater improvement, with N-Gain scores for literacy (0.449) and numeracy (0.439) exceeding those of the control group (0.268 and 0.236, respectively). Additionally, prior knowledge had a significant effect on numeracy outcomes, but not on literacy. The study recommends integrating PBL into the curriculum to enhance student skills and encourages further research on motivational and sociocultural factors. PBL is demonstrated to be an innovative and relevant approach for improving the quality of education in Indonesia.